CSR Board Committee Characteristics and Corporate Tax Disclosure - Porkas Sojuangon Lubis; Enika Diana Batubara; Jihan Hidayah Putri; Yenni Ramadhani Harahap; M. Azmi Ibadurrahman Lubis (CV Media Inti Teknologi, 2025)
Background of study: Corporate tax disclosure is an essential element of transparent and sustainable governance, especially in emerging markets where concerns about tax avoidance remain prominent. CSR board committees are expected to play a role in strengthening responsible corporate behavior, including tax-related transparency. Aims and scope of paper: This paper aims to investigate the extent to which CSR board committee characteristics committee existence, member educational background, and member professional experience affect corporate tax disclosure. The scope of the study focuses on technology firms listed on the Indonesia Stock Exchange (IDX), a rapidly expanding sector facing growing expectations for responsible governance and accountability. Methods: The study employs a quantitative research design using secondary data obtained from annual reports and sustainability reports. A purposive sampling approach yielded 40 technology firms. Corporate tax disclosure was measured through a structured disclosure index, while CSR committee characteristics were operationalized using categorical and numerical indicators. Multiple regression analysis was conducted to test the proposed hypothese. Result: : The results show that the existence of a CSR committee, along with the educational level and experience of its members, has a positive and significant effect on corporate tax disclosure. These findings highlight the importance of CSR governance structures in promoting transparent tax practices. Conclusion: The study concludes that enhancing CSR committee competencies can strengthen tax disclosure quality. Firms and regulators should consider reinforcing CSR governance standards to support ethical and sustainable corporate behavior.